Driving sustainability in the automotive industry: bio-coated materials and modern strategies - Daniel Mendanha; Denise Carvalho; Mário Silva; Sofia Silva; Pedro Ferreira; Raquel Rodrigues; Carla J. Silva; Cristina Oliveira; Rita Marques (Academia Materials Science)
The environmental concerns associated with the automotive industry have been rising in recent years, driven by strict legislation, and increasing customer demands. In response, the sector is gradually transitioning toward a more sustainable approach in the selection of materials. The preference has been for recyclable and bio-based materials. Today, bio-based materials are continually entering the market, with an increased focus on leveraging byproducts or waste from other industries to support environmental sustainability and the circular economy. These alternative materials typically consist of a textile substrate that can be modified regarding its composition and often incorporate bio-based coatings as alternatives to leather and petroleum-derived materials. The coating of the textile material can be performed through various direct and indirect methodologies, depending on attributes, economic feasibility, and the desired quality of the final material. Before introducing new materials into the automotive industry, several legislative standards and tests must be satisfied. Moreover, given the increasing need for recycling and product life-cycle consideration, there is a growing pursuit of mono-material approaches to facilitate and improve the recycling of the selected materials. This review explores and summarizes the current sustainability challenges in the automotive industry and highlights the bio-coated materials and alternative strategies currently under exploration.